2010
DOI: 10.1038/nature09590
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant macroH2A suppresses melanoma progression through regulation of CDK8

Abstract: Cancer is a disease consisting of both genetic and epigenetic changes. While increasing evidence demonstrates that tumour progression entails chromatin-mediated changes such as DNA methylation, the role of histone variants in cancer initiation and progression currently remains unclear. Here, we report that the histone variant macroH2A (mH2A) suppresses tumour progression of malignant melanoma. Loss of mH2A isoforms, histone variants generally associated with condensed chromatin and fine-tuning of developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
369
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 357 publications
(388 citation statements)
references
References 30 publications
(53 reference statements)
16
369
1
2
Order By: Relevance
“…6,7,31,36,38 We observed that pLKO-sh-CDK8-2 works more efficiently in depleting CDK8 than pLKO-sh-CDK8-1 in AN3 CA cells, thus pLKO-sh-CDK8-2 was used for further analysis in this work. Besides these two sh-CDK8 constructs, an independent set of sh-CDK8 constructs that target different sequence of hCDK8 mRNA using the same pLKO vector, designated as "sh-CDK8-S#1" to "sh-CDK8-S#5" were purchased from Sigma: sh-CDK8-…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…6,7,31,36,38 We observed that pLKO-sh-CDK8-2 works more efficiently in depleting CDK8 than pLKO-sh-CDK8-1 in AN3 CA cells, thus pLKO-sh-CDK8-2 was used for further analysis in this work. Besides these two sh-CDK8 constructs, an independent set of sh-CDK8 constructs that target different sequence of hCDK8 mRNA using the same pLKO vector, designated as "sh-CDK8-S#1" to "sh-CDK8-S#5" were purchased from Sigma: sh-CDK8-…”
Section: Discussionmentioning
confidence: 88%
“…Thus to further examine the notion that CDK8 inhibits the growth of endometrial cancer cells, we depleted CDK8 in AN3 CA cells by transducing the cells with pLKO.1-shRNAs, which were previously shown to specifically target CDK8. 6,7,31,36,38 Similar construct targeting GFP (sh-GFP) was used as the negative control. Transduced cells were selected by puromycin for over 2 wk, and the efficiency of CDK8 knockdown was verified by qRT-PCR and western blot.…”
Section: Tumor-suppressive Effects Of Cdk8 In Endometrial Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown H2A.Z to be overexpressed and play a role in other tumor types; however, these studies either focused solely on H2A.Z.1 or did not clearly distinguish between the isoforms. 5 We have demonstrated that both H2A.Z isoforms are highly expressed in melanoma and that high expression levels correlate with shorter survival of patients. Although we do not exclude a role for H2A.Z.1 in melanoma pathogenesis, we identified a distinct role for H2A.Z.2 as a mediator of melanoma cell proliferation.…”
mentioning
confidence: 89%
“…4 We have previously identified the histone variant macroH2A as a tumor suppressor in melanoma that directly regulates expression of the cyclin-dependent kinase CDK8. 5 In addition, the chromatin remodeler ATRX, a negative regulator of macroH2A, can be used as a prognostic marker of melanoma. 6 Recently, we have reported a role for another variant of the H2A family, namely H2A.Z.2, in promoting proliferation of melanoma cells.…”
mentioning
confidence: 99%